2011
DOI: 10.1007/s00586-011-2017-x
|View full text |Cite
|
Sign up to set email alerts
|

How do idiopathic scoliosis patients who improve after surgery differ from those who do not exceed a minimum detectable change?

Abstract: Introduction The minimum detectable change (MDC) of the SRS-22 subtotal score is 6.8 points. With the use of this value, patients who have undergone surgery for idiopathic scoliosis can be dichotomized into two groups: the successful (S) group (those who have reached or exceeded this limit) and the unsuccessful (Un-S) group (those in whom the change was smaller). The aim of this study was to analyze the clinical and radiological differences between these patient groups, as well as those related to the surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…As the mean change from pre-to postOperation was less than MCID in all these cohorts, we can conclude that clinically significant changes did not occur despite not being able to calculate QY 26,33,35,37,38 The single cohort that had clinically worse preoperative pain than those unaffected was corrected to within the normal range. At 2 years postsurgery, the CI for the difference between this cohort and the unaffected data were 0.09 to -0.28.25…”
Section: Linical Changesmentioning
confidence: 87%
“…As the mean change from pre-to postOperation was less than MCID in all these cohorts, we can conclude that clinically significant changes did not occur despite not being able to calculate QY 26,33,35,37,38 The single cohort that had clinically worse preoperative pain than those unaffected was corrected to within the normal range. At 2 years postsurgery, the CI for the difference between this cohort and the unaffected data were 0.09 to -0.28.25…”
Section: Linical Changesmentioning
confidence: 87%
“…The PDS system is amenable to use by surgeons and preserving the integrity of posterior ligaments and facet joints [ 5 , 6 ]. With the inherent characteristics of intervertebral motion preserved, the pedicle-screw-based PDS could be used as an adjunct to spinal fusion to facilitate graft fusing [ 7 - 9 ], or as a stand-alone system for non-fusion procedures [ 10 - 13 ]. Moreover, Gillet et al [ 14 ] proposed extending dynamic fixation one level above the fusion segments to palliate the development of accelerated degeneration at the adjacent level.…”
Section: Introductionmentioning
confidence: 99%
“…Accepting these possible confounding factors, when our MSRSI domain scores were converted to SR22r using regression equations described by Lai and colleagues, the group as a whole scored lower than current normative values for the SRS22r questionnaire for healthy adolescents in pain (3.4 vs. 4.3) and self-image (3.4 vs. 4.2) preoperatively. A prospective study by Bago et al 47 reported that although statistically significant improvements occurred in pain, selfimage, and mental health domains of the SRS22, only 52% of cases improved by above the MID for subtotal score. Functional domain scores were higher in our cohort than in normative data (4.5 vs. 4.0).…”
Section: Discussionmentioning
confidence: 99%